Public health systems under attack in Canada: Evidence on public health system performance challenges arbitrary reform - Guyon, Ak’ingabe (Can J Public Health, 2016)
Public health is currently being weakened in several Canadian jurisdictions. Unprecedented and arbitrary cuts to the public health budget in Quebec in 2015 were a striking example of this. In order to support public health leaders and citizens in their capacity to advocate for evidence-informed public health reforms, we propose a knowledge synthesis of elements of public health systems that are significantly associated with improved performance. Research consistently and significantly associates four elements of public health systems with improved productivity: 1) increased financial resources, 2) increased staffing per capita, 3) population size between 50,000 and 500,000, and 4) specific evidence-based organizational and administrative features. Furthermore, increased financial resources and increased staffing per capita are significantly associated with improved population health outcomes. We contend that any effort at optimization of public health systems should at least be guided by these four evidence-informed factors. Canada already has existing capacity in carrying out public health systems and services research. Further advancement of our academic and professional expertise on public health systems will allow Canadian public health jurisdictions to be inspired by the best public health models and become stronger advocates for public health’s resources, interventions and outcomes when they need to be celebrated or defended.